1998
DOI: 10.1038/sj.bmt.1701183
|View full text |Cite
|
Sign up to set email alerts
|

An unusual marrow transplant complication: cardiac myxoma

Abstract: Summary:We report a right atrial myxoma which suddenly developed in a thalassemic patient after allogeneic bone marrow transplantation. The tumor was first detected by echocardiography on day +47 after transplant and the patient underwent surgical removal of the myxoma on day +103. The post-operative course was uneventful, and at more than 3 years from the event, he is alive and well, cured from his congenital disease, with no detectable intra-cardiac tumor. The onset of the myxoma in the early post-transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 11 publications
(9 reference statements)
0
10
0
Order By: Relevance
“…As confirmed by serial echocardiography and repeated surgical excision, both initial [13,28,69] and recurrent atrial myxomas evidently grow particularly rapidly: estimate of average growth is 1.8 cm and 14 g per year [48]. A possible relationship has been suggested between sudden onset of a right atrial myxoma with rapid growth and the immunosuppressive status after allogeneic bone marrow transplantation [6].…”
Section: Discussion and Literature Overview Origin And Development Ofmentioning
confidence: 90%
“…As confirmed by serial echocardiography and repeated surgical excision, both initial [13,28,69] and recurrent atrial myxomas evidently grow particularly rapidly: estimate of average growth is 1.8 cm and 14 g per year [48]. A possible relationship has been suggested between sudden onset of a right atrial myxoma with rapid growth and the immunosuppressive status after allogeneic bone marrow transplantation [6].…”
Section: Discussion and Literature Overview Origin And Development Ofmentioning
confidence: 90%
“…15 Another case of atrial myxoma was reported after bone marrow transplantation. 16 Surgical extirpation is the treatment of choice for this condition. The risk associated with this procedure is relatively low, but some complications can occur.…”
Section: Discussionmentioning
confidence: 99%
“…1 There is one report of a patient developing an atrial myxoma after bone marrow transplantation. 2 Atrial myxomas are more common in women; 10% are familial and usually present between the third and sixth decades of life. Serious complications of atrial myxomas include embolisation and mitral valve obstruction.…”
Section: Discussionmentioning
confidence: 99%